Pemanfaatan Lubang Biopori dan Pembuatan Pupuk Kompos untuk Peningkatan Kesuburan Tanah di Desa Bukit Rawi, Kecamatan Kahayan Tengah,Kabupaten Pulang Pisau - Melliani, Mika; Maya Permata Sinta; Obet Aidit Gandi; Andi Kristian Gagah Hawino; Ollin Teja Putra; Lela Oktaria; Ciwo Ciwo; Oktaria Esteremia Putri Yore; Erta Marni Miranti; Adellia Adellia; Rema Valencia; Silva Silva; Aprianto Wirawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The 2025 Regular Kuliah Kerja Nyata (KKN) program is being carried out in Bukit Rawi village, Kahayan Tengah subdistrict, Pulang Pisau Regency. The main focus is on using biopori holes and making organic compost to improve soil fertility. The methods used include educating the community, providing training, and offering direct support. The results show that residents have gained more knowledge and skills in turning organic waste into compost. Seven active biopori holes have been created on household and demonstration lands. The community participation was very high, especially from farmers' groups and housewives. This activity is hoped to be continued independently by the community and to serve as a model for other villages in Kahayan Tengah subdistrict.